Solve the given logarithm equation ${\log _x}\left( {3{x^2} + 10x} \right) = 3$
Last updated date: 25th Mar 2023
•
Total views: 307.2k
•
Views today: 2.85k
Answer
307.2k+ views
Hint- We need to solve the given problem using basic formulae of logarithms.
Given logarithmic equation is ${\log _x}\left( {3{x^2} + 10x} \right) = 3$
$ \Rightarrow 3{x^2} + 10x = {x^3}$ $\left[ {\because {{\log }_a}b = x \Leftrightarrow b = {a^x}} \right]$
Simplifying the above equation, we get
$ \Rightarrow {x^3} - 3{x^2} - 10x = 0$
Factorization of the above equation give
$ \Rightarrow {x^3} + 2{x^2} - 5{x^2} - 10x = 0$
$ \Rightarrow ({x^2} - 5x)(x + 2) = 0$
$ \Rightarrow x(x - 5)(x + 2) = 0$
The domain of x is x>0, since x=0 and x=-2 do not lie in the domain of x.
$ \Rightarrow x = 5$ is the only solution of the given equation.
Note:
In the given problem our goal is to find x value. We have x in the base of logarithm and in the logarithmic expression. We used the formula of equivalence in logarithms $\left[ {\because {{\log }_a}b = x \Leftrightarrow b = {a^x}} \right]$ , to take x out from the base. Then we got a polynomial equation of degree 3. We solved for x value. We got three values for x out of those one is negative, one is zero and the remaining one is positive value. Logarithmic bases should be always greater than zero. So the positive value is the required x value.
Given logarithmic equation is ${\log _x}\left( {3{x^2} + 10x} \right) = 3$
$ \Rightarrow 3{x^2} + 10x = {x^3}$ $\left[ {\because {{\log }_a}b = x \Leftrightarrow b = {a^x}} \right]$
Simplifying the above equation, we get
$ \Rightarrow {x^3} - 3{x^2} - 10x = 0$
Factorization of the above equation give
$ \Rightarrow {x^3} + 2{x^2} - 5{x^2} - 10x = 0$
$ \Rightarrow ({x^2} - 5x)(x + 2) = 0$
$ \Rightarrow x(x - 5)(x + 2) = 0$
The domain of x is x>0, since x=0 and x=-2 do not lie in the domain of x.
$ \Rightarrow x = 5$ is the only solution of the given equation.
Note:
In the given problem our goal is to find x value. We have x in the base of logarithm and in the logarithmic expression. We used the formula of equivalence in logarithms $\left[ {\because {{\log }_a}b = x \Leftrightarrow b = {a^x}} \right]$ , to take x out from the base. Then we got a polynomial equation of degree 3. We solved for x value. We got three values for x out of those one is negative, one is zero and the remaining one is positive value. Logarithmic bases should be always greater than zero. So the positive value is the required x value.
Recently Updated Pages
If a spring has a period T and is cut into the n equal class 11 physics CBSE

A planet moves around the sun in nearly circular orbit class 11 physics CBSE

In any triangle AB2 BC4 CA3 and D is the midpoint of class 11 maths JEE_Main

In a Delta ABC 2asin dfracAB+C2 is equal to IIT Screening class 11 maths JEE_Main

If in aDelta ABCangle A 45circ angle C 60circ then class 11 maths JEE_Main

If in a triangle rmABC side a sqrt 3 + 1rmcm and angle class 11 maths JEE_Main

Trending doubts
Difference Between Plant Cell and Animal Cell

Write an application to the principal requesting five class 10 english CBSE

Ray optics is valid when characteristic dimensions class 12 physics CBSE

Give 10 examples for herbs , shrubs , climbers , creepers

Write a letter to the principal requesting him to grant class 10 english CBSE

List out three methods of soil conservation

Epipetalous and syngenesious stamens occur in aSolanaceae class 11 biology CBSE

Change the following sentences into negative and interrogative class 10 english CBSE

A Short Paragraph on our Country India
